2017
DOI: 10.20471/acc.2017.56.04.04
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of Airborne Dust as a Result of Plaster Cast Sawing

Abstract: Plaster splints are used daily in surgical and orthopedic fields in order to immobilize injured children and adults. The aim of this study was to measure the aerodynamic diameter and concentration of dust particles in the air caused by sawing plaster splints (calcium sulfate dehy-drate). We performed fractional measurements of airborne dust particles. The measured particles, which can potentially be inhaled, may have a specific negative effect on human health. Measurements were conducted in laboratory research… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
2
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 14 publications
0
2
0
Order By: Relevance
“…We also wanted to see the behaviour of the indoor PM 1 fraction over these months (that is, under the same local outdoor meteorological conditions), as – to the best of our knowledge – only a few studies reported any PM levels in indoor environments in Croatia, mostly urban, including schools and universities ( 10 , 11 ), or related to simulated or real occupational exposure in hospitals ( 12 ) and metal workshops ( 13 ), but none in rural background environment.…”
mentioning
confidence: 99%
“…We also wanted to see the behaviour of the indoor PM 1 fraction over these months (that is, under the same local outdoor meteorological conditions), as – to the best of our knowledge – only a few studies reported any PM levels in indoor environments in Croatia, mostly urban, including schools and universities ( 10 , 11 ), or related to simulated or real occupational exposure in hospitals ( 12 ) and metal workshops ( 13 ), but none in rural background environment.…”
mentioning
confidence: 99%
“…Health hazards associated with nanoparticles have been extensively reported [ 24 ]. As shown in Table 4 , for the Inlets and Outlets evaluated in this study, the airborne particles corresponding to the sizes of 10–100 nm accounted for 77–86% of all particles, significantly higher than that at workplaces investigated in previous studies [ [25] , [26] , [27] , [28] ]. In addition, the contribution of nanoparticles (100 nm) in airborne particles during heat treatment was higher than in other workplaces, indicating that there are many fine particles present even when the mass concentration of airborne particles is low.…”
Section: Discussionmentioning
confidence: 53%